Food Security Media Analysis (FOMA) - International Food Policy Research Institute (International Food Policy Research Institute, 2012)
Tracks the extent to which media coverage and information gaps impact food price spikes. The data generated by the tool can be used to determine whether the information portrayed by the media is accurate, and look at media coverage in relation to other factors that affect food prices.